INSOLVENCY TEST SEBAGAI SOLUSI PREVENTIF DALAM KONSTRUKSI HUKUM KEPAILITAN DI INDONESIA - Putri Rahmawati (2023)
In the status quo, it is very easy for the requirements for bankruptcy applications in Indonesia to make it easy for creditors and debtors with bad intentions to apply for bankruptcy. In addition, the definition of bankruptcy and the parameters for the minimum amount of debt are not clear. Even until now, there is no definite mechanism to prove the debtor's inability to repay their debts. Thus, this problem also has implications for the easy risk of legally going bankrupt for debtors even if the debtor is still in a solvent condition and has good faith. This is what makes the financial health, total assets, and good faith of debtors need to be considered through the Insolvency Test mechanism so as not to harm debtors who are still in good financial condition and have good faith. Then, the problem being analyzed is related to legal protection for debtors who are still solvent and in good faith who have not been accommodated optimally. The type of research used in this study is a type of normative legal research with statute and conceptual approaches. The data source used is secondary data with primary, secondary and tertiary legal materials. The results of this study indicate that revision or renewal of Law No. 37 of 2004 on Bankruptcy and Suspension of Payment Obligation (Bankruptcy Law) is necessary by including the Insolvency Test method as an attempt to prove the debtor's financial health and good faith. This has the urgency to embody progressivity, justice, and legal certainty for the parties, especially for debtors, so that debtors who still have good financial conditions and good faith can be saved from bankruptcy.